1986
DOI: 10.1203/00006450-198605000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Assisted Ventilation on Creatinine Clearance and Hormonal Control of Electrolyte Balance in Very Low Birth Weight Infants

Abstract: ABSTRACT. Because renal function and electrolyte balance are commonly altered in premature infants, particularly those requiring ventilatory support, we studied the influence of assisted ventilation on renal electrolyte and water excretion in infants with birth weights less than 1501 g during the 2 days after birth. Twenty-two infants receiving assisted ventilation, either as intermittent mandatory ventilation or nasal continuous positive airway pressure, were compared with 21 spontaneously ventilating infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Again no significant differences were found. This contrasts with the data of Leslie et al [21], who found a negative effect of artificial ventilation on glomerular filtration using creatinine clearance. In their study the reported values for creatinine clearance are surprisingly low for infants needing artificial ventilation as well as for those breathing spontaneously.…”
Section: Discussionmentioning
confidence: 56%
“…Again no significant differences were found. This contrasts with the data of Leslie et al [21], who found a negative effect of artificial ventilation on glomerular filtration using creatinine clearance. In their study the reported values for creatinine clearance are surprisingly low for infants needing artificial ventilation as well as for those breathing spontaneously.…”
Section: Discussionmentioning
confidence: 56%
“…Although mechanical ventilation with positive pressure in VLBW infants is associated with a lower creatinine clearance and higher values of urinary arginine vasopressin and osmolality [29], we did not exclude infants receiving this therapy from our analysis. All 23-to 28-week GA infants received courses of ampicillin/gen- Sense 5′-CAACAGCCCTTTCTTCCACATG-3′ 303 Antisense 5′-TGTCATAGCCTCTCTTCATCCTGG-3′ GAPDH Sense 5′-GCTGAACGGGGAAACTCACTG-3′ 307 Antisense 5′-TCCACCACCCTGTTGCTGTA-3′ tamicin or vancomycin/cefotaxime, as clinically indicated.…”
Section: Generalmentioning
confidence: 98%
“…Positive pressure ventilation had a small effect on CL which was model dependent. Although Van der Heijden [23] has documented an absence of any effect of ventilation on renal clearance in premature neonates at PNA 3 days, others [22,29,30] have demonstrated a reduction of renal clearance in premature neonates in their first 2 weeks of life. This reduction may be mediated through lowered renal function due to decreased atrial natriuretic peptide and increased antidiuretic hormone production attributable to right atrial pressure receptors which are influenced by altered thoracic pressures during positive pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%